Pengaruh Suplementasi Enzim Bromelain Terhadap Performa Pertumbuhan Belut (Anguilla Bicolor) - Mohammad Faizal Ulkhaq, S.Pi., M.Si; Darmawan Setia Budi; Syarifa Bintang Maharani; Boedi Setya Rahardja (Journal of Aquaculture Science, 2023)
The eel (Anguilla bicolor) is an economically significant but slow-growing fish. This research aims to determine the GR, SGR, feed efficiency, and FCR values of Anguilla bicolor fed supplemental bromealin feed. The method employed was a completely randomized design (CRD), which was analyzed using an ANOVA with a 95% confidence level and subsequently evaluated by Duncan (DMRT). Enzymes derived from pineapple have a significant impact on feed conversion ratio and feed efficiency. However, neither the GR nor SGR parameters exhibited a significant change. P4 with GR 0.38 0.03 g/day, SGR 0.95 0.03%/day, FCR 1.97 0.15, and EPP 50.9 4, or 17%, was the most effective treatment in this study.